The J-waves of hypothermia - Mililis, Panagiotis; Bazoukis, George; Bakalakos, Athanasios; Letsas, Konstantinos P. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Prominent J-waves are observed in several clinical conditions many of which are highly arrhythmogenic and may lead to ventricular fibrillation (VF) and/or sudden cardiac death. We present the case of a 34-year-old male patient with hypothermia. Prominent J-waves (Osborn waves) and prolonged QT interval was evident in nearly every lead. Early recognition of these arrhythmogenic electrocardiogram (ECG) findings and treatment of hypothermia is important to minimize the risk of arrhythmic events.